Storage Stability of Turkey Meat Sausage incorporated with Carrot and Radish under Refrigerated Storage: 10.5958/2581-6616.2020.00019.5 - Reddy, M. Naveen Kumar; Kumar, M. Shashi; Reddy, G.V. Bhaskar; Krishnaiah , N.; Reddy , N. Anitha (Journal of Meat Science, 2020)
The present study was aimed to evaluate the antioxidant and antimicrobial efficacy of raw carrot paste (RCP) and raw radish paste (RRP)each at 10 % level on aerobic packaged turkey meat sausages under refrigeration (4±1°C) for a period of 25 days. The stored sausages were evaluated for physico-chemical, microbiological and sensory characteristics at an interval of 5 days. The pH of the turkey meat sausages increased significantly (P<0.05) in both control and treated sausages under aerobic packaging. The results revealed that there was significant (P<0.05) increase in the physico-chemical parameters viz., Tyrosine value and TBARS value, as storage progressed from 0-25 days. However, the values were well below the threshold level of spoilage at the end of storage period. Standard plate counts, increased significantly (P<0.05) as storage period progressed from 0-25 days. Psychrophilic counts were not detected in the control and treated sausages at 0th day, afterwards the psychrophilic counts increased significantly (P<0.05) as storage period progressed from 5-25 days. Yeast and mold counts were not detected in any of the products throughout the entire storage period. A reduction in the sensory scores of turkey meat sausages were found as the advancement of storage. Based upon the results, it can be concluded that addition of raw carrot paste (RCP) and raw radish paste (RRP) each at 10 % level would not only extends the shelf life by protecting the product longer against oxidative rancidity but also had higher acceptability than control.